Polyhydroxyalkanoates production from ethanol- and lactate-rich fermentate of confectionary industry effluents - Rangel, Catarina; Carvalho, Gilda; Oehmen, Adrian; Frison, Nicola; Lourenço, Nídia D.; Reis, Maria A.M. (International journal of biological macromolecules, 2023)
Polyhydroxyalkanoate (PHA) production has been the focus of considerable research to increase productivities and reduce production costs. In this study, a fermented confectionary industry wastewater was used as feedstock for mixed microbial culture PHA production. The feedstock was dominated by lactate and ethanol (60–90 % of all soluble fermentation products). The culture selection reactor was inoculated with municipal activated sludge and was operated at an organic loading rate (OLR) of 100 Cmmol·L−1·d−1, achieving a robust PHA-accumulating enrichment, which produced up to 52.6 ± 0.4 wt% of PHA in accumulation assays. An OLR increase in the culture selection stage to 150 Cmmol·L−1·d−1 led to a PHA content of 59.1 ± 0.6, a yield of 0.93 ± 0.01 Cmol-PHA·Cmol-S−1 and a productivity of 0.93 ± 0.01 g-PHA L−1·h−1. A correlation analysis of the impact of ethanol concentrations from 3.19 to 20.3 Cmmol·L−1 in the reactor showed that ethanol inhibited PHA production rate and yield and the consumption of other carbon sources available. Microbial community analysis revealed the increase of Amaricoccus genus during the bioreactor operation time, a known PHA accumulator. The produced polymer was poly(3-hydroxybutyrate) with an average molecular weight of 4.3 × 105 Da and a polydispersity index of 1.88. [Display omitted] •Fermented confectionary industry effluent was high in ethanol and acetate.•A robust PHA accumulating mixed culture was selected using the fermented feedstock.•The culture was able to adapt to significant shifts in feedstock composition.•Multiparametric correlation analysis evidenced ethanol inhibition in PHA production.•Competitive PHA productivity/yield attained despite high lactate/ethanol levels.